A frequency domain study on deck isolation effectiveness in control of wave-induced vibration of offshore jacket platform. (15th February 2023) - Sarkar, Nilarghya; Ghosh, Aparna (Dey)
Abstract: A frequency domain-based investigation is carried out on the effectiveness of deck isolation under wave-induced vibrations of offshore jacket platforms. The deck isolation layer comprises laminated rubber bearings and supplemental damping in the form of linear viscous dampers. The jacket platform is modelled by a multi-degree-of-freedom lumped mass system. The frequency response functions (FRFs) are formulated and then presented for an example jacket platform, with and without deck isolation. The power spectral density functions of the deck and jacket cap responses are obtained for the Pierson-Moskowitz (PM) wave spectrum. The effects of deck isolation are studied for several combinations of isolation layer flexibility and damping. The chief deduction from the study is that by providing adequate damping in the isolation layer, the value of which for a given jacket platform is determined by parameters such as the isolation layer flexibility and the intensity of wave loading, the wave-induced vibrations of the deck may be significantly mitigated, even under extreme sea states. Here, the isolation layer damping prevents response amplification from taking place, which is possible as deck isolation causes the structural frequencies to be nearer to that of the wave loading. Highlights: Efficacy of isolation strategy in control of wave-induced deck responses studied. Transfer function formulation of deck-isolated system response provided. Deck isolation performance under wide range of isolation layer flexibility explored. Possibility of response amplification due to deck isolation exhibited. Significance of isolation layer damping in response mitigation shown.